1995
DOI: 10.1088/0953-8984/7/34/009
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductivity in a-SeTe

Abstract: Ab!;tract In-quadrature freqiency-resolved photocurrent (PRPC) measurements were perforined on amorphous SeTe films between 20 K and 290 K. and as a function of excitation intensity. These measuremenrs yield lifetime distributions directly. The results show that the reclimbination kkes place between distant pain and that there is a continuous distribution of stat!s within the mobility gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…Values for lying between 0.5 and 1 is an indication for a continuous distribution of traps in the energy gap. Similar results have been reported by Kaplan before [20].…”
Section: Frequency Resolved Photoconductivity (Frpc) and Response Timsupporting
confidence: 92%
See 2 more Smart Citations
“…Values for lying between 0.5 and 1 is an indication for a continuous distribution of traps in the energy gap. Similar results have been reported by Kaplan before [20].…”
Section: Frequency Resolved Photoconductivity (Frpc) and Response Timsupporting
confidence: 92%
“…Photoconductivity in each plot is normalized with respect to its maximum value. The photoconductivity response time is calculated using the relation ½ ¾ Ñ Ü where Ñ Ü is the frequency at which photoconductivity shows a peak in its value [20]. From the FRPC data at different intensities of illumination and at different temperatures it is found that the position of Ñ Ü shifts to higher frequencies with increasing temperature or intensity.…”
Section: Frequency Resolved Photoconductivity (Frpc) and Response Timmentioning
confidence: 99%
See 1 more Smart Citation
“…For the range of intensities investigated, we have plotted the variation of ln τ with ln g for the two compositions in figure 5. From the relation τ = Ag ν [17], the value of the exponent ν has been evaluated. For all the samples it lies between 0.5 and 1.…”
Section: Discussionmentioning
confidence: 99%
“…Carrier lifetime has been measured by the frequency resolved photo current (FRPC) technique [15,16]. The lifetime of the carriers in the sample is related to the frequency corresponding to the peak (f max ) in the frequency dependence of a.c. photoconductivity through the relation τ = 1/2πf max [15,17].…”
Section: Experimental Methodsmentioning
confidence: 99%